Moving from efficacy to effectiveness: implementing the drug market intervention across multiple sites - Saunders, Jessica M. (Criminology & public policy, 2017)
In 2012, the editors of CPP published an exchange about the Drug Market Intervention (DMI) in High Point, NC, concluding that it may be a promising approach to crime control but questioning whether it could be implemented across different settings. In this effectiveness study, we followed a cohort of seven sites that participated in a Bureau of Justice Assistance–sponsored DMI training to assess implementation and outcomes. Three sites were not able to implement, and implementation fidelity varied across the four sites that did implement. Of the four sites that held at least one call‐in, only one was successful at reducing overall and drug crime (by 28% and 56%, respectively). This works out to an implementation rate of 57% with an average overall crime reduction of 16% (treatment‐on‐the‐treated) or 4% (intent‐to‐treat). The results of this study demonstrate the importance of replication and the careful study of implementation fidelity prior to wide dissemination.